Carboxymethylcellulose and carrageenan as stabilizers in ginger-turmeric ice creams: physicochemical and sensory properties - Mukhammad Fauzi; Soni Sisbudi Harsono; Iren Laurensa Prawidya Resmasari (Brazilian Journal of Food Technology)
Abstract Ice cream is a frozen dessert usually made from dairy products, such as milk, often combined with other ingredients prepared by freezing and churning. Other ingredients can be added in the preparation of ice cream to increase its functional properties. Consuming ginger and turmeric extracts can be beneficial to health for containing several bioactive compounds. Ice cream production requires stabilizers to obtain suitable properties. Thus, this research aims to establish the type and amount of stabilizers to produce ice cream with good properties that appeal to panelists. This research was conducted based on a Randomized Group Design (RGD) with two factors: the type of stabilizer (CMC/carboxymethyl cellulose, and carrageenan) and the amount of stabilizers (0.1%; 0.3%; and 0.5%). The following parameters were analyzed: overrun; lightness; melting rate; antioxidant activity; texture; preference of color, taste, flavor/aroma, texture; and overall ice cream preference score. The best treatment is established by an effectiveness test. Ginger-turmeric ice cream with good and profitable properties was produced when treated with a CMC stabilizer at a concentration of 0.1%. Ginger-turmeric ice cream showed the following parameter values: overrun of 38.87%; lightness of 69.42; texture of 11.87 mm/50 g/10 seconds; melting rate of 1.71 g/70 g/minute; antioxidant activity of 68.31%; sensory values of color preference of 5.32; aroma, 4.60; taste, 5.00; texture, 5.08; and overall preference score of 5.08.